Experimental study of the patellar tendon fixation strength after its reconstruction - Vyrva, Oleg; Skoryk, Ivan; Karpinsky, Mykhaylo; Karpinska, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2020)
Modular replacement is an adequate method of treatment after removal of proximal tibia tumors. However, there are problems with the restoration of the knee joint function, its extensor mechanism. Objective: to determine the strength of patellar ligament fixation under modeling on the knee joint of a pig. The reconstruction of the extensor mechanism was made with a nylon tape or attachment tube to fix the patellar ligament to the proximal tibia tuberosity. Methods: on the preparations of the pigs knee joints, the reconstruction of the extensor mechanism was simulated in two series of the experiment: I — grafting of the patellar ligament using a nylon tape; II — grafting with attachment tube, previously fixed to the proximal part of the tibia. The samples were tested for strength under the influence of a tension loading, the value of which was gradually increased until the patellar ligament was torn off from the tibia. The obtained results were processed statistically. Results: samples of the I series withstood the load before failure on average 1.4 times less than in the II series (t = –4.820; p = 0.001). The average values of the load that caused the tearing of the patellar ligament were significantly different, however, the maximum value of the series of breaking load of series I did not intersect with the minimum value of the series of data of series II. Detachment of the ligament from the patella occurred due to the eruption, and not the destruction of the suture material. Conclusions: the attachment tube is 1.4 times stronger (p < 0.01) than nylon tape. Due to this, the knee joint movements, and operated limb weight bearing can be started in the early postoperative period, thereby reducing the number of complications and improving the functional outcomes of surgeries in patients with proximal tibia tumors.